Improvement of EduBPMN Transformation Rules from an Empirical Validation - Díaz, Eduardo (2024)
EduBPMN method allows the generation of graphical components from a BPMN model complemented with the UML class diagram. This article proposes the improvement of five transformation rules of the EduBPMN method from an experiment developed in 2019, with the improved transformation rules an experiment was developed that was executed by 31 subjects where the results of two metrics were obtained, (i) the correctness of the rules, where the subjects had to map BPMN to graphic components intuitively through an experimental problem, had a positive result (87.50%), (ii) the satisfaction of the generalization of the rules, had a positive result in its Perceived Ease of Use (93%), Perceived Usefulness (95%), and Intention to Use (96%). This article provides positive results on the five new improved rules of the EduBPMN method, which is used to map BPMN to graphical components.